FAKTOR-FAKTOR YANG MEMPENGARUHI KETIDAKPATUHAN PENGEMUDI SEPEDA MOTOR TERHADAP KEWAJIBAN MENYALAKAN LAMPU UTAMA PADA SIANG HARI - Nurul Huda; Loso l (LPPM Universitas Pekalongan, 2011)
Compliance and legal awareness is one important element for the establishment of order and security in society, including in-traffic activity. In fact, there are many reasons and factors that influence people to comply or not comply with traffic laws in this field especially in terms of the primary obligation of lights during the day. Therefore necessary socialization should be done accompanied by a strict law enforcement efforts. Key words: compliance with the law - enforcement – order